Books Tales of Nakamura [review of Brilliant! Shuji Nakamura and the Revolution in Lighting Technology (Johnstone, B.; 2007)]. - Riordan, M.
This book not only provides a biography of Shuji Nakamura, developer of the bright blue light-emitting diode (LED), but it also offers an insightful first look at several key players in a solid-state lighting industry that is already grossing more than 4 billion dollars annually.